Development Strategy for the Hill Districts of Uttarakhand - Surabhi Mittal; Gaurav Tripathi; Deepti Sethi (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Uttarakhand, in spite of being a small state, has certain key features that make it distinct from other states of the country and highlights its potential for development. However, development has predominantly been in the plains, and the hill districts have been left behind. All the hill districts have subsistence farming as their main economic activity. Due to subsistence livelihood, migration and a remittance economy operate in the hill districts. They are land-locked with huge distances between the markets and resources. Because of these constraints, traditional agriculture cannot be the lead sector for development. Thus the state faces the challenge of promoting livelihoods to minimize migration through local employment and income generation, and to enhance the quality of life of people living in villages. The positive features of these hill districts are that they have enormous potential for tourism, a suitable climate for high-value agriculture, and a pleasant environment due to 60 pert cent forest cover. These have to be harnessed for a development strategy. The development strategy for Uttarakhand hills should be based on developing brand equity under the name of Organic Green State and an Uttarakhand Brand Equity Fund should be set up. This can be achieved by working towards this common goal through infrastructure development, tourism promotion, agriculture diversification, poultry- and wool-based livelihoods, and SMEs based on the above that capture linkages with industry and tourism.
Keywords: R11; R38; 330; Uttarakhand; Development Strategy; Organic Green State